2021
DOI: 10.1007/s10815-021-02327-6
|View full text |Cite
|
Sign up to set email alerts
|

The change in endometrial thickness following progesterone exposure correlates with in vitro fertilization outcome after transfer of vitrified-warmed blastocysts

Abstract: Purpose To determine if the change in endometrial thickness following exogenous progesterone (P) initiation correlates with outcome following autologous transfer of a single thawed blastocyst. Methods The study is a retrospective observational cohort study conducted at a private fertility center. Patients scheduled for thawed blastocyst transfer received artificial endometrial preparation (artificial cycle FET) and underwent serial ultrasonography. The main outcomes were the rate of ongoing pregnancy (fetal he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 20 publications
5
8
0
Order By: Relevance
“…To cite an example, in a study by Haas et al, the continuing pregnancy rate was significantly higher in EC group whereas Jin et al reported that the CPR was higher in cycles that had no EC [7,13]. In contrast with Jin et al, Kaye showed that the CPR was higher in EC group [14]. In accordance with our study, Olgan determined that CPR did not differ between EC and noncompaction groups [15].…”
Section: Discussionsupporting
confidence: 87%
“…To cite an example, in a study by Haas et al, the continuing pregnancy rate was significantly higher in EC group whereas Jin et al reported that the CPR was higher in cycles that had no EC [7,13]. In contrast with Jin et al, Kaye showed that the CPR was higher in EC group [14]. In accordance with our study, Olgan determined that CPR did not differ between EC and noncompaction groups [15].…”
Section: Discussionsupporting
confidence: 87%
“…In five studies of FET-HRT ( 13 , 14 , 22 , 23 , 31 ) and one study with fresh oocyte donation ( 26 ), ECR was defined as the rate of change in EMT between the day of progesterone administration and the day of ET. In 7 other FET-HRT studies ( 12 , 18 20 , 24 , 25 , 28 ), ECR was defined as the rate of change at which EMT changed from the end of estrogen-only phase to the ET or the day before the ET.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 7 prospective studies and 11 retrospective studies were included. Of these, 11 studies ( 17 , 18 , 20 22 , 24 , 26 29 , 31 ) did not find a statistically significant association between endometrial compaction and pregnancy outcomes, whereas in 5 studies ( 12 , 19 , 23 , 25 , 30 ) better pregnancy outcomes were reported. In contrast, Bu et al.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…When there is no visible physical abnormality in the endometrium, these measures have used as an indicator of the receptivity of the endometrium receptivity (Sadek et al, 2022), (Krief et al, 2019). It's generally understood that the proper thickness of endometrial and vascularity are required for a successful pregnancy, and multiple theses have reported poor pregnancy scores in women with weak, poorly vascularized endometrium (Kaye et al, 2021). Although physicians disagree on the ideal endometrial thickness for conception, there is agreement that endometrial thickness less than 7 mm on ultrasound is typically regarded sub-optimal for embryo transfer and is linked to a lower chance of pregnancy (Alaa, et al, 2021)..…”
Section: Introductionmentioning
confidence: 99%